The Impact of an Effective Rehabilitation System on the Academic Performance of Special needs persons - Olanrewaju, Sunday (Journal of Innovation and Research in Primary Education, 2024)
This study looked at how well functioning rehabilitation programme affect special needs students’ academic performance in Federal College of Education (Special), Oyo. A descriptive research design was employed for the study. The population of the study consisted of all the Academic staff from the School of Special Education, Federal College of Education (Special), Oyo. The sample size for the study was fifty (50) academic staff randomly selected from various departments in special education. A Self-developed questionnaire titled: Impact of an Effective Rehabilitation System on the Academic Performance of Special Needs Persons (IERSAPSP) was used by the researcher for data collection. The instrument was validated and the reliability coefficient 0f 0.86 was realized which implies that the instrument was reliable. Three research questions guided the study. The data collected were organized and analyzed using descriptive statistics frequency count and percentage. The findings showed that persons with special needs find it very difficult to adapt to school life and show signs of inappropriate or what might be considered immature behavior, but with effective rehabilitation system this will enable them to reach and maintain their optimal physical, sensory, intellectual, psychological, and social functional levels. It was recommended among others that the Government at all levels should ensure that a reasonable percentage of the Education Trust Fund Allocation is made available for the education of students with disabilities.